2017
DOI: 10.1038/s41598-017-11649-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of sonication pre-treatment and cation valence in the sol-gel transition of nano-cellulose suspensions

Abstract: Sol-gel transition of carboxylated cellulose nanocrystals has been investigated using rheology, SAXS, NMR and optical spectroscopies to unveil the distinctive roles of ultrasound treatments and addition of various cations. Besides cellulose fiber fragmentation, sonication treatment induces fast gelling of the solution. The gelation is independent of the addition of cations, while the final rheological properties are highly influenced by the type, concentration and sequence of the operations since the cations m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
(37 reference statements)
1
31
0
Order By: Relevance
“…Microenvironmental mechanical stress has been demonstrated to induce apoptosis in cancer cells (Cheng, Tse, Jain, & Munn, ) and warnings about physical trauma have been reported on the European Standards EN ISO 10993‐5 for the evaluation of Biomedical devices by direct contact tests in vitro (ISO 10993‐5, ). Enhanced physical stress can be expected for CNC‐HMs used for this study since they are made of a homogeneous and soft material, as indicated by its rheological parameters (storage and elastic moduli) and the shear‐thinning behavior (Maestri, Abrami, et al, ). These characteristics make the CNC hydrogels easily injectable and suitable for in vivo applications such as drug and cell delivery, absorption of exudates, and exchange of fluids.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Microenvironmental mechanical stress has been demonstrated to induce apoptosis in cancer cells (Cheng, Tse, Jain, & Munn, ) and warnings about physical trauma have been reported on the European Standards EN ISO 10993‐5 for the evaluation of Biomedical devices by direct contact tests in vitro (ISO 10993‐5, ). Enhanced physical stress can be expected for CNC‐HMs used for this study since they are made of a homogeneous and soft material, as indicated by its rheological parameters (storage and elastic moduli) and the shear‐thinning behavior (Maestri, Abrami, et al, ). These characteristics make the CNC hydrogels easily injectable and suitable for in vivo applications such as drug and cell delivery, absorption of exudates, and exchange of fluids.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of internalized CNCs further supports the quantitative data of Figure , which demonstrate the nontoxicity of CNCs. Sonication and cross‐linking by cations entangle CNCs in soft hydrogels, the elastic modulus of which depends on the ratio charge/radius of the positively charged cross‐linker (Maestri, Abrami, et al, ). Ca 2+ has been extensively used as cross‐linker of polysaccharides and, recently, to produce CNC hydrogels (Dong, Snyder, Williams, & Andzelm, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the addition of surfactants to CNF suspension enhanced the gelation properties even in low concentrations (Quennouz et al 2016). Most recently, Maestri et al (2017) have shown that application of ultrasounds breaks the TEMPO-oxidized cellulose fibrils in the amorphous region producing isolated nanofibrils which suspension forms weak but uniform and transparent gel (Maestri et al 2017). This separation of fibrils avail the interaction of polymeric surface with water molecules effecting the rheological properties.…”
Section: Mechanical Properties Of Nanopapersmentioning
confidence: 99%